International Work-Time Trends: The Emerging Gap in Hours - Hayden, Anders (Just Labour, 2003)
This paper examines historical and recent trends in average annual work hours. The shared long-term decline in annual hours appears to be giving way to a growing divergence among OECD nations, with notable differences between several European nations and the United States. Significant differences among nations exist in annual vacation entitlements and are emerging with regard to the workweek. Competing notions of work-time flexibility held by employers and employees are an important new element in recent work-time debates, as is the related trend toward individualised forms of work-time reduction. Some European countries with pioneering work-time regimes are reviewed. The paper concludes by raising the question of how Canada can resist the American long-hours model and catch up with leading-edge practices.